Exploring the effects of topoisomerase II inhibitor XK469 on anthracycline cardiotoxicity and DNA damage - Keresteš, Veronika; Kubeš, Jan; Applová, Lenka; Kollárová, Petra; Lenčová-Popelová, Olga; Melnikova, Iuliia; Karabanovich, Galina; Khazeem, Mushtaq M; Bavlovič-Piskáčková, Hana; Štěrbová-Kovaříková, Petra; Austin, Caroline A; Roh, Jaroslav; et al. (Toxicological sciences, 2024)
Anthracyclines, such as doxorubicin (adriamycin), daunorubicin, or epirubicin, rank among the most effective agents in classical anticancer chemotherapy. However, cardiotoxicity remains the main limitation of their clinical use. Topoisomerase IIβ has recently been identified as a plausible target of anthracyclines in cardiomyocytes. We examined the putative topoisomerase IIβ selective agent XK469 as a potential cardioprotective and designed several new analogs. In our experiments, XK469 inhibited both topoisomerase isoforms (α and β) and did not induce topoisomerase II covalent complexes in isolated cardiomyocytes and HL-60, but induced proteasomal degradation of topoisomerase II in these cell types. The cardioprotective potential of XK469 was studied on rat neonatal cardiomyocytes, where dexrazoxane (ICRF-187), the only clinically approved cardioprotective, was effective. Initially, XK469 prevented daunorubicin-induced toxicity and p53 phosphorylation in cardiomyocytes. However, it only partially prevented the phosphorylation of H2AX and did not affect DNA damage measured by Comet Assay. It also did not compromise the daunorubicin antiproliferative effect in HL-60 leukemic cells. When administered to rabbits to evaluate its cardioprotective potential in vivo, XK469 failed to prevent the daunorubicin-induced cardiac toxicity in either acute or chronic settings. In the following in vitro analysis, we found that prolonged and continuous exposure of rat neonatal cardiomyocytes to XK469 led to significant toxicity. In conclusion, this study provides important evidence on the effects of XK469 and its combination with daunorubicin in clinically relevant doses in cardiomyocytes. Despite its promising characteristics, long-term treatments and in vivo experiments have not confirmed its cardioprotective potential.
Keywords: DNA Topoisomerases, Type II; Anthracyclines; dexrazoxane; Daunorubicin; XK469; doxorubicin; anthracyclines; cardiotoxicity; Doxorubicin; krysa rodu Rattus; zvířata; daunomycin; antracykliny; DNA-topoisomerasy typu II; králíci; Quinoxalines; poškození DNA; Rats; Topoisomerase II Inhibitors; DNA Damage; kardiotoxicita; Animals; topoisomerase II; chinoxaliny; inhibitory topoisomerasy II; Cardiotoxicity; Rabbits; Antibiotics, Antineoplastic; protinádorová antibiotika